Genetic Profile and Microsatellite Instability in a Case of Secondary Esophageal Squamous Cell Carcinoma 12 Years After Allogeneic Hematopoietic Stem Cell Transplantation for Aplastic Anemia. Issue 4 (May 2020) - Akiyama, Masaharu; Yamaoka, Masayoshi; Ohyama, Wataru; Yokoi, Kentaro; Ashizuka, Shuichi; Aizawa, Daisuke; Ikegami, Masahiro; Suzuki, Hideaki; Ozaki, Koji; Ida, Hiroyuki; Yuza, Yuki
Abstract : We report on a 16-year-old Japanese boy in whom an esophageal squamous cell carcinoma (ESCC) developed 12 years after allogeneic hematopoietic stem cell transplantation was performed for aplastic anemia. A high frequency of microsatellite instability was detected in samples of ESCC. Moreover, the detection of pathogenic variants, including single nucleotide substitution of TP53 (c.346C>T) and BRCA2 (c.6952C>T) and splicing of KDM6A (c.1194+2T>G), suggest that the development of ESCC in the patient was triggered by impairment of checkpoint and repair for DNA damage and epigenetic modification through accumulation of gene mutations induced by chronic graft-versus-host disease and prolonged administration of tacrolimus. Abstract : Supplemental Digital Content is available in the text.